2014
DOI: 10.1111/1462-2920.12581
|View full text |Cite
|
Sign up to set email alerts
|

The meningococcal autotransporter AutA is implicated in autoaggregation and biofilm formation

Abstract: Autotransporters (ATs) are proteins secreted by Gram-negative bacteria that often play a role in virulence. Eight different ATs have been identified in Neisseria meningitidis, but only six of them have been characterized. AutA is one of the remaining ATs. Its expression remains controversial. Here, we show that the autA gene is present in many neisserial species, but its expression is often disrupted by various genetic features; however, it is expressed in certain strains of N. meningitidis. By sequencing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 52 publications
0
68
2
Order By: Relevance
“…Thus, NalP regulates biofilm formation. NhhA and NadA are cell-associated trimeric ATs with a role in adhesion to eukaryotic cells (Capecchi et al, 2005; Scarselli et al, 2006), whilst AutA is a monomeric AT involved in bacterial autoaggregation, a function that affects biofilm structure (Arenas et al, 2015). The remaining AT, AutB, has not been characterized yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, NalP regulates biofilm formation. NhhA and NadA are cell-associated trimeric ATs with a role in adhesion to eukaryotic cells (Capecchi et al, 2005; Scarselli et al, 2006), whilst AutA is a monomeric AT involved in bacterial autoaggregation, a function that affects biofilm structure (Arenas et al, 2015). The remaining AT, AutB, has not been characterized yet.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the genes for most ATs in N. meningitidis is prone to phase variation by slipped-strand mispairing at short nucleotide repeats (Turner et al, 2002; van Ulsen et al, 2006; Arenas et al, 2015). Besides, expression of several AT genes, e.g., ausI and autA , can be prevented in certain lineages by genetic disruptions, such as deletions or frame-shift mutations, possibly evolved by selection pressure imposed by the immune system (van Ulsen et al, 2006; Arenas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The autA gene is distributed across the neisseriae, and the in vitro phenotype accompanying its expression, i.e., the formation of small microcolonies consistent with those identified by Sim and colleagues (Sim et al, 2000), led the authors to suggest that AutA expression may be important to establishing the carrier state (Arenas et al, 2015). In their study, conducted on a panel of mostly invasive meningococcal lineages, the authors showed that autA expression was restricted to a narrow range of strains, due to disruption of the open reading frame by premature STOP codons, insertions or deletions.…”
Section: The Role Of Adhesinsmentioning
confidence: 83%
“…AutA is a phase-variable, self-associating, DNA-binding meningococcal autotransporter, which mediates bacterial autoaggregation (Arenas et al, 2015). The autA gene is distributed across the neisseriae, and the in vitro phenotype accompanying its expression, i.e., the formation of small microcolonies consistent with those identified by Sim and colleagues (Sim et al, 2000), led the authors to suggest that AutA expression may be important to establishing the carrier state (Arenas et al, 2015).…”
Section: The Role Of Adhesinsmentioning
confidence: 99%
See 1 more Smart Citation